Combined effects of blood flow restriction training and nutritional intervention on muscle adaptations: a systematic review and meta-analysis - Zhao, B.; Zhai, H. (Frontiers in Nutrition, 2026)
Background: Blood flow restriction (BFR) training induces muscle hypertrophy and strength gains under low-load conditions by restricting blood flow. While BFR reduces mechanical stress on joints, the associated metabolic stress and discomfort may limit training performance. Certain nutritional supplements may enhance BFR training effects, but the existing evidence remains inconclusive.